Movie Still From The Pearl - RKO Radio Pictures:::Creator::::::::::::
The Pearl movie still of Kino (Pedro Armendariz), Juana (Maria Elena Marques) and Coyotito resing under trees. A Caption reads: THE PEARL The family rests after walking all night. This scene filmed in Acapulco de Juarez, Guerrero, Mexico, North America. RESTRICTED USE Original in safe